Anaemia of inflammation preceding dyspnoea, dry cough and weight loss in primary pulmonary lymphoma - Ami Schattner; Ariel Rokach; Fiona Vernea; Maria Spector; Kalman Filanovsky (European Journal of Case Reports in Internal Medicine)
Introduction: There is little information in the literature on the early, sub-clinical stage and laboratory test results in patients with primary mucosa-associated lymphoid tissue (MALT) lymphoma of the lung, a rare disease. Case description: In a 75-year-old man, an open lung biopsy-confirmed diagnosis of primary pulmonary lymphoma was preceded by almost six months of anaemia of inflammatory disease and monocytosis without any pulmonary symptoms. When he developed a dry cough, increasing dyspnoea and marked weight loss, these changes deepened and became associated with reactive thrombocytosis; markedly increased ferritin and C-reactive protein (positive acute-phase reactants), as well as reduced albumin and transferrin (negative acute-phase reactants). Globulins increased, due to an increase in the alpha1, alpha2 and gamma fractions, and mild hyponatraemia developed due to the syndrome of inappropriate antidiuretic hormone secretion (SIADH) secondary to the intrathoracic disease. All these changes were completely reversible following successful treatment and complete remission. Conclusion: The previously unreported detailed laboratory features of early, sub-clinical and advanced primary pulmonary lymphoma are presented. When a potentially susceptible patient develops an unexplained anaemia of inflammatory disease, primary pulmonary lymphoma should be added to the differential diagnosis.